Perlindungan Hukum Terhadap Pelapor Tindak Pidana Narkotika - Zikron, M.; Haryadi, Haryadi; Monita, Yulia (PAMPAS: Journal of Criminal Law, 2022)
This study aims to: 1). To find out and analyze, the form of legal protection that can be done for Narcotics Crime Reporters in the Jambi City Region 2). To find out and analyze the obstacles faced in providing legal protection to Narcotics Crime Reporters in the Jambi City Region. The problems discussed are: 1). Forms of Implementation of Legal Protection Against Narcotics Crime Reporters in the City of Jambi ? 2). Obstacles Faced in Providing Protection to Whistleblowers of Narcotics Crimes in the Legal Territory of Jambi City? In this study, the author uses an empirical juridical research method, namely "research in the form of field studies starting from primary data to find theories regarding the process of occurrence and the process of working the law. 1). Primary data is data obtained directly from the first source. Primary data obtained through interviews are data obtained directly in the field through the respondents who have been carried out. 2). Secondary data is data obtained from official documents, diaries, and so on. Secondary data obtained from existing books. The results of the study contain: Forms of Implementation of Legal Protection Against Narcotics Crime Reporters in the Jambi City Region, Law Number 31 of 2014 concerning the Protection of Witnesses and Victims is expected to provide protection for witnesses and whistleblowers whose core is justice and truth and is able to guarantee certainty, order, law enforcement and protection for witnesses and respect for human rights which are the rights of a witness to a crime that has occurred. Abstrak Penelitian ini bertujuan: 1). Untuk mengetahui dan menganalisis, bentuk perlindungan hukum yang dapat dilakukan untuk Pelapor Tindak Pidana Narkotika Di Wilayah Kota Jambi. 2) Untuk mengetahui dan menganalisis, kendala yang dihadapi dalam pemberian perlindungan hukum terhadap Pelapor Tindak Pidana Narkotika di Wilayah Kota Jambi. Permasalahan yang dibahas adalah: 1). Bentuk Pelaksanaan Perlindungan Hukum Terhadap Pelapor Tindak Pidana Narkotika Di Wilayah Kota Jambi? 2) Kendala Yang Di Hadapi Dalam Pemberian Perlindungan Terhadap Pelapor Tindak Pidana Narkotika di Wilayah Hukum Kota Jambi? Dalam penelitian ini penulis menggunakan metode penelitian yuridis empiris yaitu “penelitian berupa studi-studi lapangan yang bertitik tolak dari data primer untuk menemukan teori-teori mengenai proses terjadinya dan mengenai proses berkerjanya hukum. 1). Data primer adalah data yang diperoleh langsung dari sumber pertama. Data primer diperoleh melalui wawancara Adalah data yang diperoleh secara langsung dilapangan melalui para responden yang telah dilakukan. 2) Data sekunder adalah data yang diperoleh dari dokumen-dokumen resmi, buku harian, dan seterusnya. Data sekunder diperoleh dari buku-buku yang ada. Hasil penelitian berisi tentang: Bentuk Pelaksanaan Perlindungan Hukum Terhadap Pelapor Tindak Pidana Narkotika Di Wilayah Kota Jambi, Undang-undang Nomor 31 Tahun 2014 tentang Perlindungan Saksi dan Korban diharapkan dapat memberikan perlindungan bagi saksi dan pelapor yang berintikan pada keadilan dan kebenaran serta mampu menjamin kepastian, ketertiban, penegakan dan perlindungan hukum bagi saksi serta menghargai Hak Asasi Manusia yang menjadi hak bagi seorang saksi tindak pidana yang telah terjadi.